I'll stop the world : a novel - Thoman, Lauren (Mindy's Book Studio, 2023)
When a crazy twist of fate sends him back to 1985, Justin Warren meets determined optimist Rose Yin, and in a series of events that reverberate through multiple lifetimes, they have a week to get him unstuck in time and solve a murder that hasn't happened yet.